REVOLUSI EKAJAYA: MENDUNIA DARI DESA - Narita Yuri Adrianingsih; Happy Hana Asamai, Ninsi Nofita Seli Illu, Yuyun Illu Olang, Simon Tande, Freds Maara, Dominggus Fam (JOURNAL OF COMMUNITY DEDICATION, 2025)
Globalization of food has shifted consumer preferences toward practical, nutritious snacks with storytelling value. However, local village potentials are often marketed only as low-value raw materials. Ekajaya Village, Pantar Tengah District, Alor Regency, has main commodities such as cashew nuts, corn, and papaya that have not been optimally processed. This community service program aimed to increase the added value of local products through food processing training. The implementation included identifying village potentials and training 10 local youths to produce crispy cashews, corn chips, and papaya chips. The results show that participants were able to produce innovative snacks with good taste, simple techniques, and longer shelf life. Their enthusiasm confirmed the successful transfer of knowledge and skills. This program is expected to become an initial step in transforming local products into modern snacks with higher economic value while opening wider market opportunities at the national level.